STRATEGI KOMUNIKASI PARIWISATA WAY KAMBANG EDUPARK DALAM MEMBANGUN BRAND AWARENESS - Afifah Agustin; Heru Anisa Agustiani; Rintu Kaloka (Bapelitbang Kabupaten Batang, 2022)
This study aims to analyze how the communication strategy of Way Kambang Edupark managers applies to branding their names such as through Instagram social media, persuasive communication, and promotions. The research data were obtained through interviews, observations, and literature. This research method uses a qualitative descriptive method that allows and understands the problem in more depth. The purpose of this study was to determine the application of communication strategies and branding tactics by the Way Kambang Edupark tourism manager in attracting public awareness. The results showed that the development of Way Kambang Edupark branding through Instagram social media, persuasive communication, and promotions was considered effective to increase public awareness of tourism which was still relatively new.